O papel do ESG (ambiental, social e governança) nas empresas transnacionais e as implicações na responsabilização civil por acidente de trabalho - Moraes, Heloísa Polizel de Oliveira (2023)
The present work aims to analyze the purpose of disclosing that a company complies with the principles and rules laid down in environmental, social and governance (ESG) legislation and its implications. The objective is to demonstrate the importance of observing the constitutional guidelines already established for the achievement of business activity, including transnational ones. We opted for doctrinal, legal and jurisprudential and data bibliographical research, using the deductive method. The research is justified by the growing demand for critical consumption of goods and services that adopt minimum postures of respect for laws and the environment, social and governance with sustainability, indicating the present work to demonstrate its concepts and the procedural implication of advertising therefrom arising, especially with regard to civil liability for accidents at work and occupational disease.